Drivers of rainfall trends in and around Mainland Southeast Asia - Skliris, Nikolaos; Marsh, Robert; Haigh, Ivan D.; Wood, Melissa; Hirschi, Joel; Darby, Stephen; Quynh, Nguyen Phu; Hung, Nguyen Nghia (Frontiers in Climate, 2022)
Observational rain gauge/satellite and reanalysis datasets since the 1950s are evaluated for trends in mean and extreme rainfall in and around Mainland Southeast Asia (MSEA). Rain gauge data indicate strong increases exceeding 50% in both annual mean precipitation and various extreme precipitation indices over Vietnam and the northwestern part of the peninsula since 1979. The remote influence of ENSO may partially explain the recent precipitation trend towards a more intense regional hydrological cycle, in response to predominant La Niña states over recent decades. Increasing precipitation in MSEA is also associated with increased monsoon intensity in southeast Asia and a northward shift of the monsoon activity centre towards MSEA over 1979-2018. Warming-driven evaporation increases were obtained over the adjacent seas typically feeding precipitation over MSEA associated with a shift towards predominantly positive phases of the two major natural climate variability modes of the tropical Indian Ocean, namely the Indian Ocean Dipole and the Indian Ocean Basin Mode. A moisture budget analysis using ERA5 re-analysis data showed increasing oceanic moisture transports along the typical winter and summer moisture pathways towards the MSEA. However, results show that during summer the major part of increased moisture from the oceanic moisture sources ends up as precipitation over the oceanic regions adjacent to MSEA with ERA5 not being able to produce the observed positive trends in summer continental precipitation. On the other hand, ERA5 reveals pronounced increases in winter precipitation over the MSEA, in accordance with rain-gauge data, associated with strongly increasing transport of moisture originated from the western tropical Pacific and the South China Sea.